Metabolic Syndrome according to Three Definitions in Hammam-Sousse Sahloul Heart Study: A City Based Tunisian Study. (4th August 2014) - Boumaiza, Imen; Omezzine, Asma; Romdhane, Meriem; Rejeb, Jihène; Rebhi, Lamia; Bouacida, Lobna; Neffati, Souhir; Ben Rejeb, Nabila; Ben Abdelaziz, Ahmed; Bouslama, Ali
Abstract : Objectives . Metabolic syndrome (MetS) is a major risk factor of CVD. The aim of the present study is to determine the prevalence of the MetS, its components, and its different profiles according to NCEP-ATP III 2001, IDF 2005, and JIS 2009 definitions in Hammam-Sousse Sahloul Heart Study (HSHS). Study Design . The study involved 1121 participants (364 men and 757 women; sex-ratio = 0.48; mean age = 47.49 ± 16.24 years) living in Hammam Sousse city, located in the east of Tunisia. Methods . Anthropometric parameters, blood pressure, lipids levels, glycemia, insulinemia, and body mass index were measured. Statistical analyses were performed by SPSS16.0. Results . The percentage of participants who had MetS defined according to NCEP ATP III, IDF 2005, and JIS 2009 definitions was respectively, 29.5%, 38.4%, and 39.6%. With regard to gender, the prevalence of MetS is higher in men than in women according to IDF 2005 definition (38.5% men versus 38.3% women, P = 0.961 ) and according to JIS 2009 definition (41.8% men versus 38.6% women, P = 0.307 ), whereas, according to NCEP ATP III definition, the prevalence of MetS is higher in women than in men (30% versus 28.6%, P = 0.627 ). The prevalence of MetS increased with increasing age according to the three definitions (P < 0.001 ) and peaked in the oldest age group (≥70 years) according to IDF 2005 and JIS 2009. Furthermore, a significant difference in the prevalence of MetS components according to gender was observed. Indeed, the abdominal obesity is the most frequent MetS compound in women group, but hypertension and low HDL-C are the most frequent in men. In addition, according to the three definitions, the most frequent MetS profile in our study is "higher waist circumference, hypertension, and low HDL-C." Conclusion . The high prevalence of MetS is a serious public health problem in Hammam-Sousse Sahloul community. Higher waist circumference, hypertension, and low HDL-C were the most frequent profile in our study.